2015
DOI: 10.1021/acs.est.5b03639
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-Scale Spatial Models of Diesel Exhaust Concentration Profile Using 1-Nitropyrene and Other Nitroarenes

Abstract: With emerging evidence that diesel exhaust exposure poses distinct risks to human health, the need for fine-scale models of diesel exhaust pollutants is growing. We modeled the spatial distribution of several nitrated polycyclic aromatic hydrocarbons (NPAHs) to identify fine-scale gradients in diesel exhaust pollution in two Seattle, WA neighborhoods. Our modeling approach fused land-use regression, meteorological dispersion modeling, and pollutant monitoring from both fixed and mobile platforms. We applied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 64 publications
1
22
1
Order By: Relevance
“…Concentrations of PAHs in PM 10 (range: 3.2-222.7 ng m −3 ) in Beijing were found in previous studies to be lower than in PM 2.5 (Wang et al, 2011c). The concentration of PAHs in this study was much lower than that reported in certain other megacities, for example, Delhi, India, in the winter season of 2003 (range: 948-1345 ng m −3 ; mean: 1157 ± 113 ng m −3 from Sharma et al, 2007) and Mexico City, Mexico, in October 2002 (range: 60-910 ng m −3 ; mean: 310 ng m −3 from Marr et al, 2004). Average concentrations for total PAHs in the first 3 h filter of the day (08:30-11:30; Monday to Friday; mean: 112 ng m −3 ) were 1.5 times higher than the rest of the day and 1.6 times higher than the same first 3 h on a Sunday.…”
Section: Data Analysis and Error Evaluationcontrasting
confidence: 65%
See 1 more Smart Citation
“…Concentrations of PAHs in PM 10 (range: 3.2-222.7 ng m −3 ) in Beijing were found in previous studies to be lower than in PM 2.5 (Wang et al, 2011c). The concentration of PAHs in this study was much lower than that reported in certain other megacities, for example, Delhi, India, in the winter season of 2003 (range: 948-1345 ng m −3 ; mean: 1157 ± 113 ng m −3 from Sharma et al, 2007) and Mexico City, Mexico, in October 2002 (range: 60-910 ng m −3 ; mean: 310 ng m −3 from Marr et al, 2004). Average concentrations for total PAHs in the first 3 h filter of the day (08:30-11:30; Monday to Friday; mean: 112 ng m −3 ) were 1.5 times higher than the rest of the day and 1.6 times higher than the same first 3 h on a Sunday.…”
Section: Data Analysis and Error Evaluationcontrasting
confidence: 65%
“…Many studies in different countries have focused on studying toxic organic pollutants in PM 2.5 because they fall within the respirable size range for humans (Sharma et al, 2007;Ringuet et al, 2012b, Farren et al, 2015. In the last decade, a major focus has been given to Chinese cities such as Shanghai, Beijing, Guangzhou, Tianjin and Shenzhen because of their population growth and geographic peripheral expansion in manufacturing capacity and energy industries which are located throughout each of the city's manufacturing zones.…”
Section: Introductionmentioning
confidence: 99%
“…As is the case in many urban, lower income neighborhoods, residents face disproportionate socioeconomic, health, and environmental challenges. There is a growing body of evidence that Georgetown and South Park are burdened with some of the worst health and air pollution disparities in the region [ 51 , 52 , 53 ]. Washington’s Environmental Health Disparities map shows that neighborhoods in the study area have the highest ranks of environmental health disparities, environmental exposures, and PM concentrations in the state [ 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Organic nitrogen functional groups appear as strong predictors of atypical (Elizabeth, NJ) EC and glaringly absent from the typical calibration. Notably, aerosols containing elevated quantities of diesel particulate matter (DPM) also contain elevated quantities of co-emitted organic nitrogen in the form of nitrated PAHs (NPAHs), several of which are used as DPM tracers (Zielinska et al 2004;Schulte et al 2015). Geographically, the Elizabeth, NJ monitoring station resides next to a toll station on the New Jersey Turnpike which seems a likely source of DPM.…”
Section: Comparative Analysis and Interpretation Of Atypical Behaviormentioning
confidence: 99%